Techno-Economic and Feasibility Assessment of Membrane-Based Wastewater Treatment and Reuse in the Automotive Industry - Sara Carvalho; Mário Eusébio; Svetlozar Velizarov (Separations)
The gradual increase in water scarcity due to depletion and/or inadequate use of water resources has affected the automotive sector. In this context, possibilities for water reuse in the pre-treatment tunnel in an automotive painting process were studied and compared with the primary goal of finding the most appropriate and economically viable water recovery solutions, considering a circular economy metric approach. To this end, an experimental campaign of aqueous effluent characterization, with determinations of most relevant chemical and physical parameters, was conducted in a company in the automotive industry sector. To reduce alkalinity and remove surfactants from the effluent of the washing phase, a cation exchange on a weak-acid-based resin was proposed along with a microfiltration membrane system with a recovery efficiency of 88%. The inclusion of subsequent ultrafiltration and reverse osmosis steps proved to be the most suitable for removing salts and biocides from the water of the cooling towers, treating approximately 68% of the water. The techno-economic feasibility was comprehensively evaluated according to the type of treatment used. A cost of EUR 245 thousand was estimated for the treatment of water from the degreasing washing phase (EUR 1.06 per manufactured car), and a cost of EUR 582 thousand was estimated for the treatment of the cooling towers’ water (EUR 2.52 per car). The estimated water income after the treatment systems’ implementation was estimated to be equal to EUR 0.07 per car for the washing stage and EUR 0.13 per car for the cooling towers. Ultimately, this study clearly demonstrated the beneficial contribution of using membrane treatment in the automotive sector’s environmental policy, leading to water reuse and much lower effluent discharge according to the principles of the circular economy.